PENGARUH STORE ATMOSPHERE, PROMOSI DAN VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PIZZA HUT AREA JAKARTA BARAT (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
This study aims to determine the effect of Store Atmosphere, Promotion, and Product Variations on Purchase Decisions at Pizza Hut Area, West Jakarta. This research is causal associative research, using multiple linear regression analysis method. The population of this research is the consumers of Pizza Hut Area, West Jakarta. The sample in this study was taken using non-probability sampling with accidental sampling method (convenience sampling) with a total of 130 respondents. The statistical tool used is multiple linear regression analysis. Data processing using SPSS statistics software. The results of this study indicate, Store Atmosphere, Promotion, and Product Variations simultaneously and significantly influence the Purchase Decision. Store Atmosphere has a significant effect on purchasing decisions. Promotion has a significant effect on purchasing decisions. Product variations have a significant effect on purchasing decisions. To improve Purchase Decisions at the West Jakarta Pizza Hut Area, West Jakarta Pizza Hut Area is expected to pay more attention to how to improve Store Atmosphere, Promotion and Product Variations in order to improve Purchase Decisions at West Jakarta Pizza Hut Area